Relationship between soil texture and soil organic matter content on mined-out lands in Berau, East Kalimantan, Indonesia - WAHJUNI HARTATI; TRIYONO SUDARMADJI (Smujo International, 2016)
Abstract. Hartati, Sudarmadji T. 2016. Relationship between soil texture and soil organic matter content on mined-out lands in Berau, East Kalimantan, Indonesia. Nusantara Bioscience 8: 83-88. Post open pit mining may in most cases leave unarable and degraded lands due to heavy soil disturbances and therefore reclamation efforts of such area should be addressed on the revitalization of the soil functions for plant growth. The capability of tropical humid soils, including post open pit mining soils, to support plant growth is largely determined by their organic matter content-nutrient pool, soil aggregation, microbial activity, etc. However, soil organic matter content is, to large extent, governed by the soil clay content which is most likely permanent. This may imply that the soil texture couple with soil organic matter content could be a sound measurement to assess the recovery stages of the mined-out lands in term of soil functions for plant growth. This research was conducted in three sites of reclamation area in Berau, East Kalimantan. Soil texture varied from moderately fine (35-40% clay) to fine (40-50% clay) and very fine (>50% clay) for the BMO, SMO and LMO sites respectively. Soil clay eluviations were found in both of SMO (8 years old revegetation) and BMO (>12 years old revegetation) sites but not in LMO site. Soil organic matter content ranged from very low (<1%) to low (1-2%) and gradually increases in line with the increase of soil clay contents. For the soils with 35-50% clay contents (SMO and BMO sites), the top 30 cm depth soil organic matter content is to some extent controlled by the soil clay contents. Clay eluviations might be used as indicators of soil pedogenic were found in moderately fine to fine soil texture. Each process occurs at >12 and 8 years old revegetation when the organic matter content reaching its maximum. The very fine soil texture does not show clay eluviations process until > 12 years old revegetation even containing the highest organic C content and reaches its maximum at 8-10 years old revegetation.